Risk Factors for Neck Nodal Metastasis in Papillary Thyroid Cancer With BRAF V600E Mutation - Han, Ying; Hou, Ling; Zhao, Bowen; Gao, Li; Li, Shiyan (Frontiers in Endocrinology, 2022)
Background: The BRAF V600E mutation is the most common genetic variant in papillary thyroid cancer (PTC), but regarding the relationship between BRAF V600E mutation in PTC and lymph node metastasis (LNM) remains controversial. Objective: To estimate risk factors for neck nodal metastasis in PTC with BRAF V600E mutation. Patients: 292 patients diagnosed with BRAF V600E mutation related PTC were admitted. Design: In this retrospective study, data from 292 patients, including clinical, molecular, ultrasonic characteristics, were analyzed. Single-factor and multiple logistic regression analyses were applied to identify risk factors for LNM in PTC with BRAF V600E mutation. Results: In the univariate analysis of all PTC patients with BRAF V600E mutation, the LNM was found to be significantly associated with age (P = 0.01), size (P = 0.000), bilaterality (P = 0.000), multifocality (P = 0.002), LNM in US (P = 0.000), capsular invasion (P = 0.01). In ultrasonic image characteristics, margin (P = 0.036), shape (P = 0.046), microcalcification (P = 0.002) were statistically significant associated with LNM. In multivariate analysis, LNM in PTCs with BRAF V600E mutation was significantly associated with age ≤45 years (OR = 1.869, P = 0.020, 95% CI = 1.106 - 3.158), size ≥1cm (OR = 3.131, P = 0.001, 95% CI = 1.578 - 6.212), LNM in US (OR = 6.962, P = 0.000, 95% CI = 2.924 - 16.572), bilaterality (OR = 1.626, P = 0.007, 95% CI = 1.142 - 2.314), ill-defined margin in US(OR = 1.980, P = 0.033, 95% CI = 1.057 - 3.709), microcalcification in US(OR = 2.786, P = 0.002, 95% CI = 1.464 - 5.303). Conclusion: This study revealed that several significant risk factors for LNM in PTCs with BRAF V600E mutation included: age ≤ 45 years, size ≥ 1cm, LNM in US, bilaterality, ill-defined margin in US, microcalcification in US.